Mitochondrial-Derived Vesicles Protect Cardiomyocytes Against Hypoxic Damage - Li, Binghu; Zhao, Hongliang; Wu, Yue; Zhu, Yu; Zhang, Jie; Yang, Guangming; Yan, Qingguang; Li, Junxia; Li, Tao; Liu, Liangming (Frontiers in Cell and Developmental Biology, 2020)
Myocardial ischemia is a condition that there is insufficient oxygen supporting the heart, which may result from myocardial infarction or even trauma-hemorrhage shock. Elucidation of the mechanism underlying myocardial ischemic damage and searching for prevention and treatment measures may be of great significance. Mitochondrial-derived vesicles (MDVs), vesicles secreted by mitochondria, are suggested to be a novel pathway for mitochondrial quality control. The present study was to investigate the role and possible mechanisms of MDVs in ischemia/hypoxia-induced myocardial apoptosis. H9C2 cardiomyocytes were used for cellular experiments. A 40% fixed blood volume hemorrhagic shock models of rats were used for constructing acute general ischemic models. MDVs were detected by immunofluorescence staining with PDH and TOM20. Exogenous MDVs were reconstituted in vitro from isolated mitochondria under different hypoxic condition. Results showed that MDV production was negatively correlated with cardiomyocyte apoptosis under hypoxia; Exogenous MDVs could inhibit hypoxia-induced cardiomyocyte apoptosis; the mechanism of MDVs protecting against hypoxia-induced cardiomyocyte apoptosis was via mitochondrial pathway by conveying Bcl-2. The present study provided evidence that MDVs could protect against hypoxic damage of cardiomyocyte via inhibiting mitochondrial apoptosis by conveying Bcl-2 partly. Our study using novel approach extends the understanding of MDVs and highlights that MDVs may be an endogenous protective mechanism under hypoxia. Strategy that can stimulate cardiomyocytes to produce cargo-specific MDVs, such as Bcl-2 containing MDVs, should be helpful for treating ischemic/hypoxic myocardial injury theoretically.